The Influence of Taxpayer Awareness and Tax Knowledge on Individual Taxpayer Compliance - Petrus Damianus Sisko Rado; Aloisius Hama (Journal of Creative Power and Ambition (JCPA), 2026)
The acceleration of sustainable national development in Indonesia relies heavily on the strength of domestic funding, where tax instruments play a vital role as the largest contributor to state revenue. This research primarily aims to evaluate and examine the influence of taxpayer awareness and tax knowledge on the compliance levels of individual taxpayers residing in the Manggarai Regency area. The study is driven by empirical conditions involving unstable compliance rates and the underperformance of individual income tax (PPh) targets, highlighting a significant gap between registered taxpayer data and actual tax return (SPT) submissions. Adopting a quantitative design with a causal associative framework, data were collected from respondents in Manggarai using Likert-scale questionnaires and processed through multiple linear regression analysis. The findings indicate that both awareness and knowledge variables, partially and simultaneously, contribute significantly and positively to enhancing tax compliance. Academically, this study reinforces tax literature within the Theory of Planned Behavior (TPB) framework while offering strategic insights for relevant institutions to optimize fiscal participation in Manggarai.